Fake news na cultura das redes: a natureza do meio é a verdade - Marin, Davi Junqueira (2022)
In the field of communication, specifically in studies on the processes of creation in communication and in culture, the relationship between medium and message has been studied since McLuhan. In the present doctoral thesis, the relationships established by this author are taken from the perspective of cyberspace and the cyberculture of fake news, raising a question associated with his theories about the vitality of the medium in relation to the importance of the truth value of messages in times of widespread misinformation. The general context of the work is in the current temporality in which we punctuate the encounter of the factual truth of the journalistic era with the dispositive truth, a discursive format intimately connected to the idea of merchandise, whose truths are built and become obsolescent at the same speed at which equipment is renewed. The problem addressed is the loss of credibility of the web for popular uses, after a journey in which the social gain was immense from the point of view of the empowerment of subjects and individuals previously excluded. This gain was not only the communicative process in its sender-receiver relationship, but from the cultural point of view of its social and collective integrations and engagements, in which new problems are brought to the surface and worked on in the same instantaneity of the entire medium, glocal real time of its digital electronics nature. The hypothesis is that fake news accelerate the obsolescence of the medium, and the evidence is in what we call social entropy added to the nature of information and communication technologies (ICT’s). Our methodological strategy rests on the theories of the semiotic square and the generative path of meaning by Eric Landowski, heir of Greimasian semiotics. So we reached the conclusion, through empirical analysis of posts extracted from the Facebook timeline